Optical Coherence Tomography Angiography of Early Stage 1a Retinal Hemangioblastoma in Von-Hippel-Lindau (Journal of Kidney Cancer, 2021)
Von-Hippel-Lindau (VHL) syndrome is characterized by focal vasoproliferative tumors of retinal capillaries called retinal capillary hemangioblastomas (RCH). These tumors are initially small and can be easily missed if not looked for carefully. As they grow, these tumors are more demanding to treat and hence the importance of detecting them early and treating them. Herein, we describe and review the optical coherence tomography angiography (OCTA) of the early-stage lesion, which suggested the involvement of superficial and a deeper retinal capillary plexus. In addition, to helping us detect these lesions earlier, OCTA may also help to understand the in vivo changes occurring at an earlier phase.